Analysis of High‐Field Energy Harvesting using Ferroelectric Materials. Issue 5 (2nd April 2014) - Patel, Satyanarayan; Chauhan, Aditya; Vaish, Rahul
Abstract: The ferroelectric family of materials is employed in a wide variety of applications, ranging from simple sensors, transducers, and actuators to micro‐electromechanical systems. The ability of these materials to combine electrical and mechanical responses has led to the establishment of many energy‐harvesting and conversion systems. However, the low energy density coupled with high frequency requirements has prevented the successful commercialization of this technology. In this regards, a new approach is presented that is capable of enhanced electro‐mechanical energy conversion by utilizing the high‐field behavior of ferroelectric materials. A novel cycle has been recommended for continuous energy generation by using the proposed method. The cycle was simulated for the commercially available lead zirconate titanate (PZT) bulk ceramic and a maximum energy density of 526 kJ m −3 per cycle was obtained for a compressive stress of 0–400 MPa and an electric field of 0.2–2.0 kV mm −1 . The energy density obtained by using the presented technique is several hundred times higher than the highest energy density previously reported. Abstract : Harvesting energy: A new approach is presented that is capable of enhanced electro‐mechanical energy conversion by utilizing the high‐field behavior of ferroelectric materials. The cycle is simulated for the commercially available lead zirconate titanate (PZT) bulk ceramic, and the energy density obtained by using the presented technique is several hundred times higher than the highest energy density previously reported.